JoJo's Bizarre Adventure: Part 4$1 (BDiamond is Unbreakable Vol. 3s - Hirohiko Araki
Let's go eat some Italian food! Josuke and the gang find themselves in hot water in a brand-new Italian restaurant thanks to its overly aggressive chef. Is he an enemy Stand user or just a foodie gone off the deep end? Plus, Josuke discovers that someone has been spying on every known Stand user in Morioh right before his absentee father, Joseph Joestar, comes to town, and the gang has to contend with Rohan Kishibe, a local mangaka who is a really bizarre individual!